2018
DOI: 10.1007/s10753-018-0886-4
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Promotes Regeneration of Inflammatory Periodontal Bone Defect in Rats via Anti-inflammation, Osteoclastogenic Inhibition, and Osteogenic Promotion

Abstract: Progranulin (PGRN) has been proved to play a crucial role in anti-inflammation and osteogenesis promotion; thus, it was hypothesized that PGRN could promote bone regeneration in periodontal disease. In this experiment, the periodontal bone defects were established in periodontitis rats; recombinant human progranulin (rhPGRN), tumor necrosis factor alpha inhibitor (anti-TNF-α), or phosphate buffer saline (PBS)-loaded collagen membrane scaffolds were implanted within defects and the rats were sacrificed at sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
5
21
0
Order By: Relevance
“…The result revealed that there was no significant difference in P65 expression between the TNF‐α and TNF‐α + PGRN stimulation groups in hPDLSCs‐sh‐TNFR1 (Figure C), whereas PGRN antagonized TNF‐α‐enhanced P65 expression in hPDLSCs‐NC (Figure B) and hPDLSCs‐sh‐TNFR2 (Figure D). These results as well as our previously revealed PGRN‐TNFR binding suggest that PGRN reverses TNF‐α‐mediated osteogenic inhibition through suppression of TNF‐α/TNFR1/NF‐κB signaling pathway.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The result revealed that there was no significant difference in P65 expression between the TNF‐α and TNF‐α + PGRN stimulation groups in hPDLSCs‐sh‐TNFR1 (Figure C), whereas PGRN antagonized TNF‐α‐enhanced P65 expression in hPDLSCs‐NC (Figure B) and hPDLSCs‐sh‐TNFR2 (Figure D). These results as well as our previously revealed PGRN‐TNFR binding suggest that PGRN reverses TNF‐α‐mediated osteogenic inhibition through suppression of TNF‐α/TNFR1/NF‐κB signaling pathway.…”
Section: Resultssupporting
confidence: 86%
“…PGRN competitively binds to TNFRs in hPDLSCs and is a natural antagonist of TNF‐α. In our study, we knocked down TNFR1 and TNFR2, respectively, to explore their role in PGRN‐mediated pro‐osteogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, various lines of evidence shows that PGRN-mediated anabolism of chondrocytes and bone formation depend on TNFR2 [34,35]. Moreover, TNFR2 activation plays a protective role in osteogenic differentiation and bone regeneration [3,4]. TNFR2 has been reported to play an important role in inflammation control, immune modulation, and neuronal protection.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activities of TNF-α are mediated through two structurally distinct receptors, tumor necrosis factor receptor 1 (TNFR1) and TNFR2. In osteoblast precursor cells, TNFR1 mediates activation of NF-κB signaling and inhibition of osteogenic differentiation after TNF-α stimulation [2], whereas TNFR2 activation by progranulin (PGRN), a TNFR2 agonist, plays a protective role in osteogenic differentiation and bone regeneration [3,4]. Furthermore, TNF-α affects behaviors of mesenchymal stem cells (MSCs) and osteoblast precursor cells in a dose and time-dependent manner [2,5].…”
Section: Introductionmentioning
confidence: 99%